Mathematical methods in physics : distributions, Hilbert space operators, variational methods, and applications in quantum physics /: distributions, Hilbert space operators, variational methods, and applications in quantum physics. (2015) - Blanchard, Philippe; Brüning, Erwin
No abstract available